God in the age of science a critique of religious reason - Philipse, Herman (Oxford : Oxford University Press, 2012)
Herman Philipse puts forward a powerful new critique of belief in God. He examines the strategies that have been used for the philosophical defence of religious belief, and by careful reasoning casts doubt on the legitimacy of relying on faith instead of evidence, and on probabilistic arguments for the existence of God.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: Religion -- Philosophy; Theism; Faith and reason; God -- Proof; Religion and science